Development of Reliable, Valid and Responsive Scoring Systems for Endoscopy and Histology in Animal Models for Inflammatory Bowel Disease. (28th March 2018) - Koelink, Pim J; Wildenberg, Manon E; Stitt, Larry W; Feagan, Brian G; Koldijk, Martin; van 't Wout, Angélique B; Atreya, Raja; Vieth, Michael; Brandse, Johannan F; Duijst, Suzanne; te Velde, Anje A; D'Haens, Geert R A M; et al.
Abstract: Background and Aims: Although several endoscopic and histopathologic indices are available for evaluating the severity of inflammation in mouse models of colitis, the reliability of these scoring instruments is unknown. Our aim was to evaluate the reliability of the individual items in the existing indices and develop new scoring systems by selection of the most reliable index items. Methods: Two observers scored the histological slides [ n = 224] and endoscopy videos [ n = 201] from treated and untreated Interleukin[IL]-10 knock-out and T-cell transferred SCID mice. Intra-rater and inter-rater reliability for endoscopy and histology scores, and each individual item, were measured using intraclass correlation coefficients [ICCs]. The Mouse Colitis Histology Index [MCHI] and Mouse Colitis Endoscopy Index [MCEI] were developed using the most reliable items. Both were correlated to the colon density and to each other and were evaluated for their ability to detect changes in pathobiology. Results: The intraclass correlation coefficients (ICCs) for inter-rater agreement (95% CIs) for the total histology and endoscopy scores were 0.90 [0.87–0.92] and 0.80 [0.76–0.84], respectively. The MCHI and MCEI were highly correlated with colon density, with a Spearman Rho = 0.81[0.75–0.85] and 0.73 [0.66–0.79], respectively, and with each other, Spearman Rho = 0.71 [0.63–0.77]. The MCHI and MCEI were able to distinguish between the experimental groups within the models, with pairwise differences between the treated and untreated groups being statistically significant [ p < 0.001]. Conclusions: These histological and endoscopic indices are valid and reliable measures of intestinal inflammation in mice, and they are responsive to treatment effects in pre-clinical studies.